The management of pancreatic cancer. Current expert opinion and recommendations derived from the 8th World Congress on Gastrointestinal Cancer, Barcelona, 2006. - Verslype, C; Van Cutsem, E; Dicato, M; Cascinu, S; Cunningham, D; Diaz-Rubio, E; Glimelius, B; Haller, D; Haustermans, K; Heinemann, V; Hoff, P; Johnston, P; et al. (2007)
This article summarizes the expert discussion on the management of pancreatic cancer, which took place during the 8th World Congress on Gastrointestinal Cancer in June 2006 in Barcelona. A multidisciplinary approach to a patient with pancreatic cancer is essential, in order to guarantee an optimal staging, surgery, selection of the appropriate (neo-)adjuvant strategy and chemotherapeutic choice management. Moreover, optimal symptomatic management requires a dedicated team of health care professionals. Quality control of surgery and pathology is especially important in this disease with a high locoregional failure rate. There is now solid evidence in favour of chemotherapy in both the adjuvant and palliative setting, and gemcitabine combined with erlotinib, capecitabine or platinum compounds seems to be slightly more active than gemcitabine alone in advanced pancreatic cancer. There is a place for chemoradiotherapy in selected patients with locally advanced disease, while the role in the adjuvant setting remains controversial. Those involved in the care for patients with pancreatic cancer should be encouraged to participate in well-designed clinical trials, in order to increase the evidence-based knowledge and to make further progress.